2017
DOI: 10.4274/jtgga.2017.0043
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Dissection in Atypical Endometrial Hyperplasia

Abstract: Objective:The rate of concomitant endometrial carcinoma in patients with atypical endometrial hyperplasia is high. We aimed to investigate the role of lymphadenectomy in deciding adjuvant treatment in patients with concomitant atypical endometrial hyperplasia and endometrial carcinoma.Material and Methods:Women with atypical endometrial hyperplasia were enrolled in this retrospective study. Lymph node dissection was performed in only some patients who gave informed consent if their surgeon elected to do so, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Furthermore, in case of incomplete surgical staging, international guidelines recommend restaging surgery with further delays if adjuvant therapy is needed [15]. Taşkın et al [8], in a retrospective study including 80 AH cases, reported a 20% rate of high-risk EC among patients undergoing surgical treatment for preoperative AH. Likewise, Whyte et al [19] reported similar results in the 67 AH patients undergoing nodal staging with 23.9% of EC patients belonging to the intermediate or high-risk group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in case of incomplete surgical staging, international guidelines recommend restaging surgery with further delays if adjuvant therapy is needed [15]. Taşkın et al [8], in a retrospective study including 80 AH cases, reported a 20% rate of high-risk EC among patients undergoing surgical treatment for preoperative AH. Likewise, Whyte et al [19] reported similar results in the 67 AH patients undergoing nodal staging with 23.9% of EC patients belonging to the intermediate or high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, 25-50% of patients subjected to hysterectomy for AH are still diagnosed with EC on the final surgical specimen [5][6][7]. This aspect has led several authors to question the possibility of preoperatively identifying the AH cases at greater risk of developing cancer and introducing sentinel lymph node (SLN) mapping also for AH patients [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…La NIE tiene un alto riesgo de progresión a CE y un potencial de enfermedad invasiva concurrente (27,31). Estudios observacionales han reportado que el carcinoma subyacente es encontrado en hasta el 60 % de los especímenes reportados con NIE (27,(32)(33)(34)(35)(36). Por ello, la histerectomía es el tratamiento de elección para la mayoría de las mujeres con HA/NIE.…”
Section: Manejo De La Neoplasia Intraepitelial Endometrialunclassified
“…Up to 60% of women presenting precancerous endometrial lesions known as atypical hyperplasia (AH) or endometrial intraepithelial neoplasia (EIN) have an undiagnosed coexistent endometrial cancer [11,12]. Since intraoperative frozen section pathology for detection of invasive disease has poor reliability and since several authors have demonstrated that hysterectomy in women with EIN may result in inadequate surgical management, some have argued to add pelvic lymphadenectomy to standard surgical management in patients with AH or EIN [13][14][15][16][17][18]. Preoperative identification of concomitant malignancies would allow for optimal surgical staging in these patients, while avoiding unnecessary lymphadenectomy in patients who do not have concurrent cancer.…”
Section: Introductionmentioning
confidence: 99%